The Impact of Resilience on Household Food Insecurity in Indonesia - Pipit Ronalia; Djoni Hartono; Misdawita Misdawita (Jurnal Ekonomi Pembangunan, 2023)
This study aims to determine the impact of resilience on household food insecurity in Indonesia. This study uses data from the National Socio-Economic Survey (Susenas) and Village Potential Data Collection (Podes) in 2018. The resilience variable is a latent variable in the form of a score formed from the pillars of access to basic services, adaptive capacity, assets, and social safety nets. Meanwhile, the food insecurity variable is approached by the Rasch Scale and Raw Score based on the Food Insecurity Experience Scale (FIES). Estimation of the resilience score was carried out using factor analysis and Structural Equation Model (SEM). After estimating the resilience score, estimation using instrument variables with the Two Stage Least Square (2SLS) method was carried out to determine the causal relationship between resilience and food insecurity. The number of community protection units (linmas) in residential villages is used as instrumental variable as a form of institutional quality approach. The results showed that the higher the level of resilience, the lower the level of household food insecurity. An increase in the resilience score by 1 unit will reduce the level of food insecurity by 0.733 units. The role of resilience in reducing food insecurity is quite large, around 22.212 relative to the average Rasch Scale of all observations.